Understanding psychological distress and social adjustment among first-year university students - Kavindi, Justine stephan; Basela, January; Martanus, Ochola O. (Journal of Indonesian Psychological Science (JIPS), 2024)
This study examined first-year university students' challenges in Tanzania by focusing on the interplay between psychological distress, coping mechanisms, and social adjustment. A mixed approach was applied, where data was collected from questionnaires and interviews with 374 students. Findings revealed a concerning prevalence of psychological distress among first-year students, with 38% experiencing severe distress, 44.5% reporting moderate distress, and only 15.5% exhibiting mental well-being upon entering the university. This distress, encompassing depression, anxiety, and stress, significantly impeded students' social adjustment. The study also revealed a significant negative relationship between psychological distress and social adjustment, coping mechanisms acting as mediators. The study highlighted the intricate dynamics among these factors. It emphasised the importance of recognising coping mechanisms as vital mediators in addressing the impact of psychological distress on students' social adjustment. This understanding can inform targeted interventions and support systems, promoting students' mental well-being, academic success, and overall satisfaction during their transition to university life. KEY WORDS: Psychological distress; coping mechanism; social adjustment; first-year university student